2020
DOI: 10.21887/ijvsbt.15.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Different Estrus Synchronization Protocols in Surti Goats

Abstract: A total of 54-adult non-pregnant Surti goats were selected and randomly divided into three equal groups (n=18 each). Two groups were put under estrus synchronization protocols, viz., Double PGF2α protocol (Inj. Dinoprost 12.5 mg, i/m, 11 days apart with natural breeding from 72-144 hours of second PG inj.) and NC Synch protocol (PG 12.5 mg - GnRH 0.004 mg - PG 12.5 mg - GnRH 0.004 mg on days 0, 8, 15 and 18, respectively with natural breeding during 19-21 days) using standard management practices and 3rd group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This proved that IVPS sponge alone coordinated the endocrine events and ovulatory estrus/conception in treated goats compared to an undisturbed control group and those exposed to buck or treated with sponge in combination with buck exposure or PG injection. These results, to some extent, concurred with reports of Kusina et al (2000), Kausar et al (2009), Parmar et al (2020) in different breeds of goats by adopting different synchronization protocols.…”
Section: Conception/ Kidding Ratessupporting
confidence: 91%
See 2 more Smart Citations
“…This proved that IVPS sponge alone coordinated the endocrine events and ovulatory estrus/conception in treated goats compared to an undisturbed control group and those exposed to buck or treated with sponge in combination with buck exposure or PG injection. These results, to some extent, concurred with reports of Kusina et al (2000), Kausar et al (2009), Parmar et al (2020) in different breeds of goats by adopting different synchronization protocols.…”
Section: Conception/ Kidding Ratessupporting
confidence: 91%
“…This technique offers tight synchrony and provides an acceptable level of fertility upon artificial or natural breeding. Synchronization of estrus in does and ewes, is achieved either by extending the luteal phase artificially with exogenous progesterone or potent progestagens and/or by reducing with prostaglandin F 2 α (PGF 2 α) or its analogs (Parmar et al, 2020. Intra-vaginal progestagen sponge impregnated with MAP and FGA is a common and traditional treatment of choice in small ruminants during the breeding and anestrus seasons and offers a convenient method to administer progestagens; perhaps a more simple method might be through oral dosing in feeds, e.g., Melengestrol acetate (MGA). Estrus response and fertility vary greatly when intra-vaginal sponges are applied, dependent on species, breed, co-treatment, management, and mating system.…”
Section: Influence Of Different Synchronization Protocols On Fertilit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The does (n=15) received 12.5mg of PGF 2α , was administered (11 days apart) to the does, that does not exhibit behavioral symptoms of oestrus. In this study, estrous periods occurring within 1 to 7 days post-injection were classified as synchronized, although other investigators (Omontese et al, 2014(Omontese et al, , 2016Famakinde et al, 2017;Bello et al, 2019;Parmar et al, 2020) have reported oestrus to begin, after an average interval of ≤50 hrs.…”
Section: Oestrus Synchronizationmentioning
confidence: 81%
“…Induction and synchronization schemes in goats include hormones, particularly melatonin, gonadotropin / gonadotropin-releasing hormone (GnRH) or agonists, progestogens, and prostaglandins, alone or in combination, administered orally, by injection, or by intravaginal devices (Kusina et al, 2000;Whitley and Jackson, 2004;Arrebola et al, 2012Arrebola et al, , 2022Parmar et al, 2020;Zuñiga-Garcia et al, 2020;Anggraeni et al, 2021;Farooqi et al, 2021;Habeeb & Kutzler, 2021;Rivas-Muñoz et al, 2021;Skliarov et al, 2021;Khandoker, 2022;Hidayah et al, 2022;Wondim et al, 2022). And the essence of the hormonal stimulation for sexual heat induction is that the luteal phase of the sexual cycle is artificially simulated by the introduction of progesterone or other progestagen-based drugs in females.…”
Section: Discussionmentioning
confidence: 99%